The older, the richer? A decomposition of wealth inequality by age subgroups - Dorothee Ihle; Andrea Siebert-Meyerhoff (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2017)
Departing from the implication of the basic life cycle model that substantial wealth inequality may arise simply because of differences in age, at first, we investigate the quantitative importance of age as a source of wealth differences in Germany using individual wealth data from the German Socio-Economic Panel for the years 2002, 2007 and 2012. Employing the well-known Gini coefficient, we decompose wealth inequality by age subgroups and calculate within- and between-group inequalities. Results suggest that more than one third of overall wealth inequality can be explained by transitory lifetime wealth differences due to age. Secondly, unconditional quantile regression is used to examine the effects of age on different points of the wealth distribution. Results reveal that the age effect is heterogeneous across the distribution. We find that age has no effect on low quantiles and an almost linear effect for the higher ones. For the middle part of the distribution, results show a hump-shaped pattern as predicted by theory. A combination of these results provides tentative evidence that an aging of the German population is associated with a growing dispersion of wealth at the upper tail of the distribution.
Keywords: D30; D31; D63; 330; age; wealth; inequality decomposition; unconditional quantile regression